Coping with risk in maritime logistics - perspectives of dry bulk shipping companies - Gou, Xueni. (2011)
Risk management is essential for any individual shipping company as well as a whole maritime logistics chain in general. Therefore, this project aims to explore how risk management is approached pertaining to the shipping industry in order to reveal risk management culture and mindset in the dry bulk shipping companies, and subsequently develop a conceptual framework for coping with risk in maritime logistics. The focus of this research project is not into any specific risk type but the general risk management culture and mindset in the shipping companies, in particular, dry bulk shipping companies.Exhaustive literature reviews and extensive Internet search were carried out to gather pertinent information. Furthermore, in-depth semi-structured interviews were also conducted with academic professionals, industry veterans and management personnel of dry bulk shipping companies.